2020
DOI: 10.1590/0102-311x00202420
|View full text |Cite
|
Sign up to set email alerts
|

Prática de chemsex entre homens que fazem sexo com homens (HSH) durante período de isolamento social por COVID-19: pesquisa online multicêntrica

Abstract: Investigar os fatores associados à prática do sexo sob o efeito de drogas (chemsex) entre homens que fazem sexo com homens (HSH) durante período de isolamento social, no contexto da pandemia da COVID-19. Inquérito multicêntrico online, aplicado aos territórios de Brasil e Portugal em abril de 2020, enquanto os dois países vivenciavam medidas sanitárias restritivas para a doença. Os participantes foram recrutados valendo-se de uma adaptação do método respondent driven sampling (RDS) ao ambiente virtual. Os dado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 23 publications
1
38
1
Order By: Relevance
“…12,29 For people who felt most isolated, the quest for sexual activity may have been a response to this prolonged period of stress, a way to cope or alleviate worries, or to find physical comfort and pleasure. 19,30 These results are also consistent with those of studies conducted in the context of other addictions during the lockdown: boredom, a lack of social contact, a loss of daily structure, reward seeking after a hard-working day, loneliness, and the search for conviviality were found as the main reasons for consuming more alcohol, tobacco, and cannabis during COVID-19 lockdowns. 24,31…”
Section: Discussionsupporting
confidence: 84%
“…12,29 For people who felt most isolated, the quest for sexual activity may have been a response to this prolonged period of stress, a way to cope or alleviate worries, or to find physical comfort and pleasure. 19,30 These results are also consistent with those of studies conducted in the context of other addictions during the lockdown: boredom, a lack of social contact, a loss of daily structure, reward seeking after a hard-working day, loneliness, and the search for conviviality were found as the main reasons for consuming more alcohol, tobacco, and cannabis during COVID-19 lockdowns. 24,31…”
Section: Discussionsupporting
confidence: 84%
“…Although slightly over half of MSM still found casual partners outside their homes, 75% had fewer partners than before the COVID-19 epidemic. This evidence highlights that the problem is not an increase or decrease in casual partners, but rather the fact that when encounters occur, they seem to be permeated with unsafe sexual practices (unknown partners, drug use, orgies, and use of ineffective prevention methods) increasing vulnerability to SARS-CoV-2 exposition and STIs simultaneously [15].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalent sexual identity among the participants in this study was homosexual, which requires a look at the vulnerabilities that are overlapping in this population group, strongly crossed by disparities in access to rights and weaknesses in socio-affective support networks, such as family. Thus, during the COVID-19 pandemic it has been identified that the LGBTQIA + population, especially among gay men (men who have sex with other men) has been more vulnerable to having their psychological wellbeing affected (21)(22) .…”
Section: Discussionmentioning
confidence: 99%